2020
DOI: 10.3389/fendo.2019.00919
|View full text |Cite
|
Sign up to set email alerts
|

Female Heart Health: Is GPER the Missing Link?

Abstract: The G Protein-Coupled Estrogen Receptor (GPER) is a novel membrane-bound receptor that mediates non-genomic actions of the primary female sex hormone 17β-estradiol. Studies over the past two decades have elucidated the beneficial actions of this receptor in a number of cardiometabolic diseases. This review will focus specifically on the cardiac actions of GPER, since this receptor is expressed in cardiomyocytes as well as other cells within the heart and most likely contributes to estrogen-induced cardioprotec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 178 publications
0
28
0
Order By: Relevance
“…Its N-terminus has a transcriptional activation function (AF-1) domain, a DNA-binding domain, and a hinge region; the C-terminus houses the ligand-binding domain and a second AF-2 domain. ERα is robustly expressed in the heart ( 132 ), VSMCs, and ECs ( 133 136 ).…”
Section: Estrogen Receptors and Their Calcium-dependent Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Its N-terminus has a transcriptional activation function (AF-1) domain, a DNA-binding domain, and a hinge region; the C-terminus houses the ligand-binding domain and a second AF-2 domain. ERα is robustly expressed in the heart ( 132 ), VSMCs, and ECs ( 133 136 ).…”
Section: Estrogen Receptors and Their Calcium-dependent Regulationmentioning
confidence: 99%
“…Many lines of evidence indicate that GPER mediates the inhibitory effect of E 2 on I Ca,L . These include inhibitory effects of E 2 (1–3 × 10 −5 M) and combined ERα/ERβ antagonists/GPER agonists (ICI182,780, tamoxifen, or raloxifene) on I Ca,L in cardiomyocytes from both WT and ERα −/− /ERβ −/− animals, as reviewed in ( 132 ). Similarly, in VSMCs, E 2 inhibits electrically induced I Ca,L ( 209 , 210 ), and ERα/ERβ antagonists/GPER agonists tamoxifen and ICI164,384 inhibit high-K + -induced contraction ( 202 ).…”
Section: Calcium Entry Inhibition By Estrogenic Agonists and Estrogenmentioning
confidence: 99%
“…Using various normotensive and hypertensive rodent models, Groban's laboratory reported that loss of ovarian estrogen by OVX leads to diastolic dysfunction and LV interstitial remodeling and hypertrophy [22,88,89]. Upon probing the local cardiac RAS in normotensive WKY rats and SHRs, we found both strain and estrogen effects with respect to cardiac ACE2 activity [20].…”
Section: Estrogen Regulation Of Ace2mentioning
confidence: 80%
“…Based on the growing evidence suggesting a sex-based difference in COVID-19 outcomes, an assessment of sexspecific hormone activity, particularly estrogen, in COVID-19 pathogenesis is warranted. Estrogen is known to modulate CVD risk and we [11] and others [18] have established a role for estrogen in regulating renin-angiotensin system (RAS) expression and activity [18][19][20][21][22][23][24][25][26][27][28]. The identification of angiotensin-converting enzyme-2 (ACE2) as the host cell receptor for the SARS-CoV-1 and SARS-CoV-2 [29] coronaviruses has brought attention to the functions of this enzyme outside the domain of its now established role in modulating angiotensin II (Ang II) metabolism as part of the RAS [30].…”
Section: Introductionmentioning
confidence: 99%
“…TNF-induced vascular inflammation (a condition which mimics the cellular stimuli induced by infiltrating immune cells), could also be attenuated by activation of GPER1, and enhanced by GPER1 antagonists, or activation of ERα, suggesting an opposing role of nuclear and extranuclear estrogen actions in the vascular endothelium ( 79 ). This finding led the authors to propose specific pharmacological options for GPER1 activation in vascular inflammation and derived atherosclerosis ( 80 ) and a specific role of this receptor in the maintenance of heart health ( 75 ).…”
Section: Gper1 Involvement In Immune-related Human Diseasesmentioning
confidence: 99%